43: NEOADJUVANT CHEMOTHERAPY OFFERS NO SURVIVAL BENEFIT FOR CT2N0M0 GASTRIC ADENOCARCINOMA. A MULTICENTRIC EUROPEAN STUDY. (23rd April 2022) - Abboretti, F; Lambert, C; Schäfer, M; Le Roy, B; Mège, D; Demartines, N; Pezet, D; Gronnier, C; Mantziari, S
Abstract: Background and aim: According to current international guidelines, the optimal treatment of stage cT2N0M0 gastric adenocarcinoma consists of preoperative chemotherapy followed by surgery. Surgery first may be suggested in selected patients, especially if considered unfit for chemotherapy. The aim of the present study was to assess if cT2N0M0 patients treated with surgery first (S) had inferior overall and disease-free survival compared to those treated with neoadjuvant chemotherapy followed by surgery (CS). Methods: A retrospective analysis was performed among 32 centers, including all consecutive patients with gastric adenocarcinoma operated between January 2007 and December 2017. Patients with cT2N0M0 stage were divided into two groups, surgery first (S) and neoadjuvant chemotherapy followed by surgery (CS). Clinico-pathological details, overall and disease-free survival were compared between the groups. Cox regression analysis was performed for long-term survival. Results: Among the 2131 included patients, 202 (9.5%) had cT2N0M0 disease: 68 (33.7%) were placed in the CS group and 134 (66.3%) in the S group. CS patients were younger (mean age 62.7 ± 12.8 vs 69.8 ± 12.1 years, P < 0.001) with WHO status 0 in 60.3% versus 34.5% in S patients ( P = 0.006). The CS group had more proximal tumors, undergoing more frequently total gastrectomy (70.6% CS vs 45.5% S, P = 0.001). The median number of resected lymph nodes was similar (22 vs 20.5, P = 0.74). R0 resection margins were obtained in 97.1% CS vs 95.5% S patients ( P = 0.72). Adjuvant chemotherapy was more often administered in CS patients (75.8% versus 29.8% in S, P < 0.001). Recurrence occured in 30.9% in CS and 18.1% in S ( P = 0.04), predominantly as distant metastases (81% CS vs 75% S, P = 0.76). Overall 5-year survival was similar between CS (74.4%, 95%CI 58.1–85.1) and S groups (66.7%, 95%CI 54.4–76.5, P = 0.73), as was 5-year disease-free survival (DFS) (64.6%, 95%CI 48.4–76.9 for CS vs 62.8%, 95%CI 50.7–72.6 for S, P = 0.82). Perioperative chemotherapy was not associated with OS or DFS in multivariate analysis. Conclusion: Patients with cT2N0M0 gastric adenocarcinoma did not present a survival or recurrence benefit if treated with CS compared to S. In accordance with esophageal cT2N0 tumors, surgery first might be a valid treatment option for these patients.